Pikukuh Igama Djawa Pasoendan and Ideology of National Values - Tendi, Tendi (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
Igama Djawa Pasoendan (IDP) is one of the beliefs in the archipelago founded by Madrais in the 19th century. Although this belief is centered in Cigugur, Kuningan, its followers are spread across a number of areas in West Java. The main teachings in the IDP are referred to as pikukuh, whose contents are mostly taken from the values ​​of local Sundanese beliefs. The study aims to describe the history of Igama Djawa Pasoendan, explain the IDP Pikukuh, and describe the teachings and national values contained in the Pikukuh. To explore the problem, the study uses the historical method which consists of heuristic, criticism, interpretation, and historiography steps. From the study it is known that the history of Igama Djawa Pasoendan is related to a figure named Madrais. In addition, it is also known that the Pikukuh of the belief system consists of a number of articles which contain the rules that must be followed by the followers of the IDP. Another thing that was obtained from the research, that the Pikukuh Igama Djawa Pasoendan turns out to contain teachings and national values which are proven by the obligation to live in harmony, not allowed to argue with other people, and others.